The Paradigm of Science According to Thomas Kuhn and Prophetic Jurisprudence - Bill Nope (Universitas Islam Indonesia, 2024)
Prophetic Jurisprudence is a legal discipline based on the epistemological foundation of Islamic teachings derived from the Quran and Hadith. The framework of prophetic jurisprudence is built upon three prophetic ethical principles: humanization (‘amar ma’ruf), liberation (nahi munkar), and transcendence (tu’minuna billah). One relevant approach for reflecting prophetic Jurisprudence is the paradigm of science proposed by Thomas Kuhn. Kuhn argues that science revolves around five key terms or concepts: paradigm, scientific revolution, pre-paradigmatic stage, normal science, and anomaly. The research questions in this study are as follows: (1) How can prophetic jurisprudence be accepted as normal science when based on Thomas Kuhn's paradigm of science? and (2) How can prophetic jurisprudence be applied to Indonesian society based on the thinking of Thomas Kuhn? This normative legal research reveals that the process of prophetic jurisprudence becoming normal science is still faced with the challenge of positioning prophetic jurisprudence as a product that needs to be systematic, logical, and open. Prophetic jurisprudence still requires tools, resources, and methods to address legal issues in the empirical world. The paradigm of prophetic jurisprudence has provided tangible examples of scientific practices through thought and research within the tradition of scientific inquiry that underlies scientific practices during a specific period. Prophetic jurisprudence is confronted with Indonesian society, which is positivist, pluralistic, and liberal and requires fast, decisive, and concrete legal solutions accompanied by sanctions.